ATC enhancement in electricity markets with GUPFC and IPFC – A comparison. (October 2016) - Kumar, Ashwani; Kumar, Jitendra
Highlights: Comparison of the ATC obtained with GUPFC and IPFC for intact and contingency cases with constant P, Q load model and ZIP load model. Results for intact and line contingency cases with simultaneous as well as single transaction cases. Comparison of results with DC/AC based method. Abstract: Available transfer capability (ATC) needs to be declared well in advance by the system operator to reserve transactions and avoid any congestion in the network. In this paper, an optimal power flow based approach has been utilized for bilateral/multi-transactions deregulated environment to obtain the ATC. The ATC has been obtained with generalized unified power flow controller (GUPFC) and interline power flow controller (IPFC) for intact and line contingency cases. The impact of ZIP load model has been evaluated on the ATC with both the devices. The main contribution of the paper is the comparison of the ATC obtained with. GUPFC and IPFC for intact and contingency cases with constant P, Q load model and ZIP load model. The results have been determined for intact and line contingency cases taking simultaneous as well as single transaction cases. The results obtained are also compared with DC/AC and PTDFs. The proposed method have been applied for IEEE 24 bus RTS.